2020
DOI: 10.1021/acs.jpclett.0c00973
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Adsorption Performance and Mechanism on Efficient Removal of Methylene Blue by Accordion-like V2CTx MXene

Abstract: Dye-bearing wastewaters leading to the water pollution and ecological upset is a crucial issue in the textile industry. Herein, we report a facile method using two-dimensional transition metal carbides (MXenes) for the removal of the methylene blue (MB) in the water. The accordion-like V 2 CT x MXene is originally demonstrated to have high and spontaneous adsorption capacity of MB at 111.11 mg•g −1 , thrice over that of Ti 3 C 2 T x as previously reported. The wide lamellar space of V 2 CT x is certain to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In addition, the maximum adsorption capacity of MB and MO onto Nb 2 CT x MXene calculated by pseudo-second-order kinetics is 526.32 and 500 mg·g –1 , which agrees well with our experimental results. Moreover, these values are larger than previous studies (shown in Table S3 in Section 5 in the Supporting Information), indicating the enhanced adsorption capacity of Nb 2 CT x MXene. , Such enhanced adsorption capacity might be originated from the layered structures of Nb 2 CT x MXene. First, the interlayer space of Nb 2 CT x MXene is as large as 0.97 nm.…”
Section: Resultsmentioning
confidence: 65%
“…In addition, the maximum adsorption capacity of MB and MO onto Nb 2 CT x MXene calculated by pseudo-second-order kinetics is 526.32 and 500 mg·g –1 , which agrees well with our experimental results. Moreover, these values are larger than previous studies (shown in Table S3 in Section 5 in the Supporting Information), indicating the enhanced adsorption capacity of Nb 2 CT x MXene. , Such enhanced adsorption capacity might be originated from the layered structures of Nb 2 CT x MXene. First, the interlayer space of Nb 2 CT x MXene is as large as 0.97 nm.…”
Section: Resultsmentioning
confidence: 65%
“…Usually, dyes in water are found in the form of ions, so they can be removed using special adsorbents. More efficient adsorption of V 2 CT x , compared to the most studied Ti 3 C 2 T x could be explained by its simpler unit cell and greater distance between the layers [182].…”
Section: Adsorptionmentioning
confidence: 95%
“…The 2D nanosheets have a large surface, on which small organic molecules (e.g., dye, drug, and pesticide) can effectively land on both surfaces, contributing to the high loading efficiency. 30,32,34 Figure 1d shows the zeta potential of Ti 3 C 2 nanosheets in aqueous solutions at different pH values. The high electronegativity of Ti 3 C 2 during pH 3−11 further verifies its good stability in a wide pH range.…”
Section: Preparation and Characterization Of Mxenementioning
confidence: 99%
“…MXene, a new type of 2D nanomaterial, is first prepared by the Gogotsi group . Benefitting from its good conductivity, hydrophilicity, and chemical stability, MXene is playing a more and more important role in the aspect of battery, energy, catalysis, environment, and biomedicine. According to previous reports, MXene materials exhibited excellent adsorption performance, which can rapidly and efficiently adsorb small molecules. In consideration of its excellent adsorption properties, as well as good water solubility and biocompatibility, MXene has drawn attention in the drug delivery and biomedicine fields in recent years. For example, Liu and colleagues designed a Ti 3 C 2 -based nanocarrier for hydrophobic drug (doxorubicin, DOX) delivery and synergistic tumor therapy . According to their study, Ti 3 C 2 possesses excellent adsorption capacity, and the drug loading rate is as high as 84.2%.…”
Section: Introductionmentioning
confidence: 99%